FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MEROKOK PADA REMAJA DI DESA NANIA - Harianti Fajar; Since Anggriani Tanarubun (Pasapua Health Journal, 2021)
Introduction: Adolescence is a period of transition from childhood to adulthood which is experiencing very rapid development and change. Development towards adulthood, children experience various changes including biological changes, psychological changes and social changes. The research objective is to analyze the factors associated with smoking behavior in adolescents. Method: This type of research is quantitative research with a cross-sectional approach, namely research directed and describing and examining the relationship of the four variables and a group of population subjects in this study 80 adolescents in Nanai Village. Results: The results of this study were obtained from 30 respondents, it can be seen that the influence of peers has an influence of 18 (60.0%), no influence of 12 (40.0%), the influence of people good old 17 (56.7%), and not good 13 (43.3%), good knowledge 25 (83.3%), not good 5 (16.7%), Smoking behavior Smoking 21 (70.0%), Not smoking 9 (30.0%). Based on the results of the chi square statistical test, the value of p = 0.000 was obtained. Because p<0.05, Ho was rejected and Ha was accepted. Conclusion: This means that there is a relationship between smoking behavior in adolescents in Nania Village.